Performance evaluation of biological selenium IV (Selenite) reduction by a pure culture of Pseudomonas stutzeri NT-I - Brink, Hendrik Gideon (University of Pretoria, 2020)
Dissertation (MSc (Applied Science: Environmental Technology))--University of Pretoria, 2020.